Du Mont Laboratories records - Du Mont Laboratories; Du Mont, Allen B. (Allen Balcom), 1901-1965.
Correspondence, television file, government hearings materials, sales and advertising files, administrative files, financial records, and other records relating chiefly to the development and commercial use of the television cathode ray tube. Includes personal papers of the firm's founder, Allen B. Du Mont. Correspondents include Keeton Arnett, Leonard Frederick Cramer, Thomas T. Goldsmith, Austin C. Lescarboura, Mortimer W. Loewi, Ernest A. Marx, Jack Poppele, William Allerton Roberts, Irving Sarlin, Albert Steadman, Herbert E. Taylor, Jr., Paul Ware, Elmer Wheeler, and C.J. Witting.
Firm devoted to electronic television and communications engineering. Organized in 1935 by Allen B. Du Mont; television receiver and manufacturing business sold to Emerson Radio and Phonograph Corporation in 1958; remainder of the firm merged with Fairchild Camera and Instrument Corporation in 1960.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arnett, Keeton -- Correspondence; Cramer, Leonard Frederick, -- 1910-1987 -- Correspondence; Goldsmith, Thomas T. -- 1910-2009 -- Correspondence; Lescarboura, Austin C. -- 1891- -- Correspondence; Loewi, Mortimer W. -- 1888-1967 -- Correspondence; Marx, Ernest A. -- Correspondence; Poppele, Jack -- Correspondence; Roberts, William A. -- 1900- -- Correspondence; Sarlin, Irving -- Correspondence; Steadman, Albert -- Correspondence; Taylor, Herbert E., -- Jr. -- Correspondence; Ware, Paul, -- 1893-1970 -- Correspondence; Wheeler, Elmer, -- 1903- -- Correspondence; Witting, C. J. -- 1915-2005 -- Correspondence; Cathode ray tubes; Electrical engineering; Electronics; Engineering laboratories; Telecommunication; Television